Metagenomic analysis of microbial consortium from natural crude oil that seeps into the marine ecosystem offshore Southern California. Issue 3 (November 2014) - Hawley, Erik; Piao, Hailan; Scott, Nicole; Malfatti, Stephanie; Pagani, Ioanna; Huntemann, Marcel; Chen, Amy; Glavina del Rio, Tijana; Foster, Brian; Copeland, Alex; Jansson, Janet; Pati, Amrita; et al.
Abstract Crude oils can be major contaminants of the marine ecosystem and microorganisms play a significant role in the degradation of its main constituents. To increase our understanding of the microbial hydrocarbon degradation process in the marine ecosystem, we collected crude oil from an active seep area located in the Santa Barbara Channel (SBC) and generated a total of about 52 Gb of raw metagenomic sequence data. The assembled data comprised ∼500 Mb, representing ∼1.1 million genes derived primarily from chemolithoautotrophic bacteria. Members ofOceanospirillales, a bacterial order belonging to theDeltaproteobacteria, recruited less than 2% of the assembled genes within the SBC metagenome. In contrast, the microbial community associated with the oil plume that developed in the aftermath of the Deepwater Horizon (DWH) blowout in 2010, was dominated byOceanospirillales, which comprised more than 60% of the metagenomic data generated from the DWH oil plume. This suggests thatOceanospirillales might play a less significant role in the microbially mediated hydrocarbon conversion within the SBC seep oil compared to the DWH plume oil. We hypothesize that this difference results from the SBC oil seep being mostly anaerobic, while the DWH oil plume is aerobic. Within theArchaea, the phylumEuryarchaeota, recruited more than 95% of the assembled archaeal sequences from the SBC oil seep metagenome, with more than 50% of the sequences assigned to members of the ordersMethanomicrobiales andMethanosarcinales . These orders contain organisms capable of anaerobic methanogenesis and methane oxidation (AOM) and we hypothesize that these orders - and their metabolic capabilities - may be fundamental to the ecology of the SBC oil seep.